PENGARUH PEMASARAN BERBASIS ISU SOSIAL TERHADAP CITRA PERUSAHAAN DAN PENJUALAN PRODUK: STUDI PADA PELAKU UMKM DI INDONESIA - Muh. Syaiful Saehu; Yanti Setianti; Teguh Setiawan Wibowo; Eigis Yani Plamularso (ITB AAS Indonesia Surakarta, 2024)
This study examines the relationship between social issues and brand image, and its impact on customer loyalty. Regression analysis was used to analyze the data collected in this research. The primary finding is that social issues have a significant positive influence on brand image. The results of the regression analysis show that social issue-based marketing can help strengthen a company's brand image. The importance of social issues in marketing is further supported by significant results from the partial T-test. While the direct impact on customer loyalty is not tested directly, improving the brand image through social issues has the potential to influence customer behavior. In conclusion, social issue-based marketing is an effective strategy for enhancing brand image and can contribute to customer loyalty. Companies that implement these practices wisely can achieve their business goals while making a positive impact on society and the environment.